Kindergarten Education and the Reading, Language and Mathematics Achievement of First Graders - Carmine, Joyce ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This study examined the effect of prekindergarten attendance on first graders' academic achievement. A literature review reported the results of other studies on the effects of early educational experiences, such as Head Start, on at-risk students' elementary school achievement. In general, these studies indicated that early educational intervention increased cognitive gains in the primary grades, but these gains were not sustained in the upper grades; that motivational and attitudinal gains from early intervention were sustained through later formal schooling; and that students from poverty areas demonstrated greater gains than did middle class children. In the present study, the Comprehensive Test of Basic Skills was administered in April of the school year to 53 first-grade students of predominantly middle to low socioeconomic class. Of these students, 10 had attended a developmental prekindergarten; the rest had not. Results indicated that there was no difference in the reading, language, and mathematics achievement between the two groups. A list of 11 references is included. (BC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Early Intervention; Elementary School Students; Grade 1.; High Risk Students; Language Skills; Mathematics Achievement; Preschool Education; Primary Education; Reading Achievement; Socioeconomic Status; Student Motivation; Project Head Start; Reports, Research